A marriage of equals - Rolls, Elizabeth (Harlequin historicals., 2021)
Having struggled so hard to become a successful business owner, Jamaica-born Psyché Winthrop-Abeni has no interest in relinquishing her freedom or property to a husband. But when gentleman Will Barclay comes to her aid, their intense connection tempts her into a thrillingly passionate temporary affair! It's the perfect arrangement until Will feels honor-bound to propose. His offer is one she's never dared to dream of, but can she trust Will enough to take the risk?